Parenting Styles - A Qualitative Analysis of the Specialized Romanian Literature - Andreea-Ionela Dohotaru; Horațiu Catalano; Adina- Roxana Baștea (Babes-Bolyai University, 2023)
Parenting approaches reflect the varied tactics and methodologies parents adopt while guiding and nurturing their offspring, including both behavioral and emotional tendencies in their relationship with their child as they mature. These approaches significantly mold children's self-worth, conduct, academic achievements, and interpersonal relations. How parents engage with their children and the way they assert their authority can leave lasting impressions on the emotional, social, and behavioral growth of the child. Thus, adopting a flexible parenting method that caters to the distinctive requirements of each child is essential for the wholesome evolution of their character, given that personality arises from a blend of genetic factors, social environments, and personal experiences. In Romania, these parenting methodologies might differ due to cultural traditions, educational histories, and familial values. There's a considerable amount of national research investigating how these parenting methods affect child development and welfare. This article intends to offer a comprehensive review of the literature that discusses parenting methodologies in a Romanian setting. This review will delve deep into the core theories of parenting approaches and pinpoint exemplary strategies. In summation, given the profound impact of parenting methods on a child's growth, it's crucial for parents to introspect and choose their child-rearing techniques thoughtfully. Employing a well-adjusted parenting approach that recognizes the individual necessities of each child is pivotal for their overall well-being and emotional stability.